2019
DOI: 10.1007/s00421-018-04062-w
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in ACL loading and strain during typical athletic movements: a musculoskeletal simulation analysis

Abstract: CLoK Central Lancashire online Knowledge www.clok.uclan.ac.uk Sex differences in ACL loading and strain during typical athletic movements: a musculoskeletal simulation analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 68 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…However, although Phinyomark et al showed that males with ITBS exhibit increased ankle eversion; experiments 1 and 3 do not support this as ankle eversion/ tibial internal rotation characteristics were not associated with ITB strain (9). The efficacy of any prophylactic or treatment intervention modality is reliant upon a clear understanding of the underlying mechanisms linked to the aetiology of the associated condition (24). Therefore, the observations provided from experiments 1 and 3 provide insight into the kinematic parameters that future effective treatment modalities should seek to attenuate.…”
Section: Discussionmentioning
confidence: 96%
“…However, although Phinyomark et al showed that males with ITBS exhibit increased ankle eversion; experiments 1 and 3 do not support this as ankle eversion/ tibial internal rotation characteristics were not associated with ITB strain (9). The efficacy of any prophylactic or treatment intervention modality is reliant upon a clear understanding of the underlying mechanisms linked to the aetiology of the associated condition (24). Therefore, the observations provided from experiments 1 and 3 provide insight into the kinematic parameters that future effective treatment modalities should seek to attenuate.…”
Section: Discussionmentioning
confidence: 96%
“…Dynamic data during the stance phase was exported from Visual 3D into OpenSim 3.3 software (Simtk.org) using a custom pipeline that allowed the inverse kinematics to be exported to match the degrees of freedom associated with the experimental model in OpenSim 27 . The standard Gait2392 Opensim musculoskeletal model was adapted to include six degrees of freedom knee joints and also an ACL bundles modelled in accordance with Sinclair et al, 27 as non-linearly elastic passive soft tissues based on the proximal (femur) and distal (tibia) insertion points of Xu et al, 40 (Figure 5ab). The model was further developed by incorporating a patella and the tibiofemoral joint was separated into medial and lateral compartment locations which were positioned at 25% and 75% of the scaled knee joint width in accordance with Barrios & Willson 41 .…”
Section: Data Processingmentioning
confidence: 99%
“…Because of the high incidence of ACL injuries in football players 15 and the poor-long term prognosis following injury, prophylactic interventions are therefore a key clinical priority 27 . Knee braces are external devices constructed in order to improve three-dimensional knee joint dynamic alignment 28 and range from semi-rigid devices incorporating uni or polyaxial hinges to more compliant sleeves designed simply to provide compression and enhance proprioception 29 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-leg landings expose the performer to higher bio-physical loads at the knee joint, due to increased vertical ground reaction force and tibial anterior shear force compared with doubleleg landings (Wang, 2011;Yeow et al, 2011). Single leg landings have been recognised for their increased injury risk, for example during hopping and landing it was observed that the loading and kinematics of the knee joint were such that the risk of ACL injury was increased, and this was shown to be greater in female athletes (Alentorn-Geli et al, 2009;Sinclair et al, 2019). It is clear from previous research that injury risk of singleleg landings is implicated in the contribution to Journal of Human Kinetics -volume 83/2022 http://www.johk.pl the greater risk of non-contact ACL injuries compared to double-leg landings (Boden et al, 2009;Yeow et al, 2011).…”
Section: Introductionmentioning
confidence: 99%